(3OhQ GdHQdeGf aj GdCfXeI GdHQdeGfjI GdeYGUQI (B:s (3VYa GdCOGA GdJTQjYj hGdQbGHj ddHQdeGf hgjefI GdSdWI GdJfajPjI (B: (3OQGSI JMdjdjI ebGQfI (B/s - (3SYjO, OGfG YHO GdcQjes ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2013)
(3Ef GdhGbY GdYedj aj GdCfXeI GdHQdeGfjI GdeYGUQI TgO GNJdGdG aj GdJhGRf Hjf GdSdWJjf GdJTQjYjI hGdJfajPjI dUGdM GdCNjQI hYQa GdacQ GdeYGUQ JQGLY GdOhQ GdJTQjYj hGdQbGHj ddHQdeGf hJONd GdSdWI GdJfajPjI aj GdeLGd GdJTQjYj HTcd cHjQ EP JeGQS Edi LGfH hXjaJgG GdJfajPjI GdhXjaI GdJTQjYjI aj fWGb hGSY ShGA cGfJ Yf WQjb GdeTGQcI aj YedjI EUOGQ GdbhGfjf HTcd aYGd Ce Yf WQjb EUOGQ GddhGFM hGdCfXeI aj GdXQha GdYGOjI hGdGSJKfGFjI hGddhGFM GdJahjVjI hGdJj dgG bhI GdbGfhf(B. (3hcGf dJVNe hXGFa GdOhdI hJZjQ eaghe GdOjebQGWjI SHHG LhgQjG hQGA JYGXe OhQ GdSdWI GdJfajPjI, cPdc TgO GdOhQ GdQbGHj ddHQdeGf JQGLYG aj GdCfXeI GdeYGUQI hde JYO gPg GdQbGHI MbjbjI haYGdI HhLg YGe hde jHb dg eYfi hUOi ceG cGf GdMGd YedjG aj GdCfXeI GdOjebQGWjI GdJbdjOjI, HeYfi BNQ de jYO GdHQdeGf bGOQG Ydi SMH GdKbI ef GdMcheI Pdc dCf GdCZdHjI GdHQdeGfjI GdMRHjI GdehGdjI ddMcheI JLYd GdHQdeGf YGFbG(B. s
(3HHdjhLQGajI (B: (3UaMI (B331-347.s
Keywords: (3GdeeGQSI GdHQdeGfjIs; (3GdQbGHI GdHQdeGfjIs -- (3bhGfjf hJTQjYGJs; (3GdSdWI GdJfajPjIs -- (3bhGfjf hJTQjYGJs